Material concreto en la comprensión de la relación número – cantidad hasta el 10 en los niños de 4 a 5 años del paralelo “B”, en la “Unidad Educativa Ángel Polibio Chaves” cantón Guaranda, provincia Bolívar, año 2023. - Supe Palate, Mercedes Guadalupe (2024)
The research project focuses on using concrete material to enhance the understanding of the number-quantity relationship among 4 to 5-year-old boys and girls in the "B" parallel of Initial II level at Ángel Polibio Chaves School in Guaranda, Bolívar province, during the academic year 2023-2024. The main objective of the project is to determine the most effective concrete material for developing the number-quantity notion in this group of children. The research adopts a qualitative approach and employs direct observation and interviews as data collection techniques. The data collection instruments include an observation form to record children's behavior and reactions during activities, as well as an interview questionnaire directed at the teacher tutor to gain deeper insight into the pedagogical approach and use of concrete material. The population consists of 200 students and 6 teachers, with a sample of 25 students and one teacher tutor. The results obtained through observation and interviews will be analyzed in relation to the pedagogical approach, children's numerical comprehension level, and the effectiveness of the concrete material used. These results have helped identify patterns, trends, and the impact of concrete material on the learning process of the number-quantity relationship in 4 to 5-year-old children, in order to develop an activity guide for Initial II "B" parallel, morning session.